Is forensic science in crisis? - Sikorski, Michał (Synthese, 2022)
The results of forensic science are believed to be reliable, and are widely used in support of verdicts around the world. However, due to the lack of suitable empirical studies, we actually know very little about the reliability of such results. In this paper, I argue that phenomena analogous to the main culprits for the replication crisis in psychology (questionable research practices, publication bias, or funding bias) are also present in forensic science. Therefore forensic results are significantly less reliable than is commonly believed. I conclude that in order to obtain reliable estimates for the reliability of forensic results, we need to conduct studies analogous to the large-scale replication projects in psychology. Additionally, I point to some ways for improving the reliability of forensic science, inspired by the reforms proposed in response to the replicability crisis.